Metacognitive Analysis of Mathematics Learning Based on Cognitive Theory for Fourth Grade Students at JQ Elementary School - Ummi Athiyyah Addany; Elly Sukmanasa (BASICA, 2025)
Fractions in elementary school mathematics are still considered difficult by students because the concepts are abstract and require deeper thinking skills. This condition causes students to experience difficulties in understanding the concepts of numerators, denominators, and solving fraction problems. Therefore, a learning approach is needed that can help students understand their own thinking processes so that learning becomes more meaningful and easier to understand. This study aims to analyze metacognitive strategies in learning fractions in mathematics for fourth-grade students at JQ Elementary School. This study used a qualitative approach with data collection techniques through observation, tests, and questionnaires of fourth-grade students at JQ Elementary School. The results showed that the metacognitive approach was able to improve students' understanding of fractions through reflection activities, discussions, and the use of concrete media in the form of pizza boards. Students became more active, critical, and able to solve mathematical problems in a more focused manner, making learning more effective and meaningful.